Foraging routes of Antarctic fur seals (Arctocephalus gazella) investigated by the concurrent use of satellite tracking and time-depth recorders - Bonnadonna, F; Mary-Anne Lea; Guinet, C (2000)
Little is known about movement behaviour in terms of route choice in Antarctic fur seals (Arctocephalus gazella). We deployed satellite transmitters and time-depth recorders simultaneously on 11 animals, and time-depth recorders with a speed recorder on 10 animals, to investigate the foraging routes of Antarctic fur seals belonging to a colony located at Iles Kerguelen (Southern Indian Ocean). The study took place during the 1997/1998 austral summer, and results indicate a preferred foraging area, with two main strategies in route choice apparent during foraging trips. In one strategy seals tended to reach an apparently known foraging ground and stopped there to feed. In the other strategy, animals performed looped trips, foraging en route and probably searching for a food patch better than the one previously exploited.